Electrochemical Evaluation of Lithium-Ion Battery with Anode of Layer-Reduced Biocarbon and Cathode of LiFePO4 - Syarif, Nirwan; Rohendi, Dedi; Sya'baniah, Nyimas (http://dx.doi.org/10.31427/IJSTT.2019.2.2.4, 2019)
The application of reduced carbon anode layer and LiFePO4 cathode was conducted in laboratory-scale battery. Both electrodes were fabricated into lithium - ion battery with LiCl electrolyte in both gel and liquid based. The carbon was prepared by using Hummer method and solvent sonification to exfoliate the carbon layer from biocarbon. The battery performance tests were carried out in potentiostat for Cyclic Voltammetry (CV) and galvanostatic measurements. The highest current of CV measurement can be obtained in the battery with reduced carbon layer anode and 20% of liquid electrolyte. It was calculated that the same battery produced the highest energy and power. Current - Voltage profile is relatively stable in CV of batteries with 40% electrolytes in both gel and liquid media. All batteries have two peaks in both anodic and cathodic. The reduction peaks show in around 0.5 and 1.5 volts. The cathodics show in around –0.5 and –1.5 volts. The best power and energy values are given by battery with rCNSO anode and 20% liquid electrolyte. Galvanostatic profiles show that the 40% electrolytes in the batteries produces a slower discharging process. It was revealed that applying anode of layer reduced biocarbon as the battery electrode caused the discharging to run faster. The highest slope value of the galvanostatic curve can be found in the battery with the electrode of oxidized starting material and 40% of gel electrolyte, while the lowest can be found in 20% gel electrolyte with the same electrode.